Charting a way ahead : - Wolfowitz, Paul (World Bank, 2005)
This is a speech given by the President of the World Bank, Paul Wolfowitz. In it, the President makes the case for making poverty history in our lifetime, especially in Africa. He stresses that anyone who faces the facts agrees there is an urgent need for action since every day, thousands of people living in extreme poverty, many of them children, die from preventable diseases. Moreover, the call to end poverty reaches across generations, continents, and nationalities. It spans religions, gender, and politics. He claims that the world is at a turning point and there are grounds for hope. The last few decades have witnessed dramatic improvement in the condition of the world's poorest people. Mr. Wolfowitz concludes that in order to find solutions for alleviating poverty, the World Bank needs to strengthen its knowledge and expertise in such areas as education, health, infrastructure, energy,and agriculture.